Evaluation of the new parameters of auditory evoked potentials (AEPs) in patients with schizophrenia spectrum disorders - Korostenskaja, Milena; Dapšys, Kastytis; Šiurkutė, Aldona; Mačiulis, Valentinas; Rukšėnas, Osvaldas; Kähkönen, Seppo (Psichologija, 2006)
The aim of the present study was to evaluate the new P300 parameters on patients with schizophrenia spectrum disorders and to compare their reliability with the commonly used P300 latency and amplitude. 56 healthy human subjects and 22 patients with schizophrenia spectrum disorders were studied. The following new parameters were considered. Some of the proposed parameters showed a more significant statistical difference in differentiating patients from controls than did the commonly used measures (latency and amplitude). We suggest that the parameters proposed by us could be helpful in differentiating schizophrenia disorder patients from controls. The use of the subtraction curve could be more preferable than the use of deviant one.
Keywords: AEPs; P300 wave; schizophrenia; schizophrenia spectrum disorders